UV-cured self-replenishing hydrophobic polymer films. (9th July 2015) - Zhang, Y.; Rocco, C.; Karasu, F.; van der Ven, L.G.J.; van Benthem, R.A.T.M.; Allonas, X.; Croutxé-Barghorn, C.; Esteves, A.C.C.; de With, G.
Abstract: Self-healing functional polymer surfaces, designed with an intrinsic and spontaneous mechanism which replenishes the damaged surfaces with the original chemical functionalities, are of great interest to maintain a high performance of the functionality and extend the life-time of materials. We report self-replenishing UV-cured hydrophobic polymer films prepared through the incorporation of methacrylate-terminated perfluorinated-dangling chains into poly(ethylene glycol diacrylate) (PEGDA)-based networks. The films are able to spontaneously and fully self-replenish the surface hydrophobicity, multiple times, upon consecutive intentional damages. The rate of recovery was found to be dependent on the glass transition temperature ( T g ) of the networks, which directly correlates to the PEG block length in the PEGDA oligomer used. This study demonstrates that an intrinsic self-replenishing mechanism can be implemented in new network architectures, created rapidly and efficiently by free radical UV-polymerization, which allows preparing self-healing functional polymer films in a faster and eco-friendlier way. Graphical abstract: Highlights: Self-healing functional surfaces with high performance and extended life-time. Rapid, efficient and eco-friendly self-replenishing UV-network architectures. PEDGA-based networks with methacrylate-terminated perfluorinated-dangling chains. Spontaneous recovery of surface hydrophobicity upon multiple/consecutive damages. Rate of surface-functionality recovery dependent on network properties.